(untitled) (PANGEEA, 2025)
There are places endowed with a force of attraction and filled with energy, which prevoke a spiritual state and a spiritual experience for most people. The present study focuses on only a part of the national minorities who live together with the Romanians in Timiş County, namely: Serbs, Hungarians, Bulgarians, and Germans. These ethnic groups represent the most important components of the total population throughout the recent history of Banat.